Pemanfaatan Ispring Suite Quizmaker Untuk Pembuatan Soal-Soal Bahasa Arab - Frida Akmalia (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2020)
Abstract: This study aims to optimize the evaluation of Arabic learning by using the Ispring Suite Quizmaker software that can be integrated directly into Microsoft Power Point with images, animations, audios, videos, sets of student ability test and their feedback. With the data that already obtained, the writer does literature study to relate some of the problems with existing theories to find relevant solutions for each issue found. As for the main problems in this study are: 1) Advances in information technology that requires techers to always provide interesting, visual, and interactive learning facilities. 2) Limitations of teacher’s knowledge in making Arabic interactive questions by using software. From some of the existing problems, there are several solutions to overcome them. One was by utilizing the Ispring Suit Quizmaker software where the teacher can make various types of questions easily such as multiple choice, right wrong, match, and stuffing.